2018
DOI: 10.1021/acs.jpcc.7b11904
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of Oxygen Vacancy Formation and Ionic Transport in Sr3Fe2O7−δ

Abstract: The elucidation of the oxygen ionic transport mechanism in atomic scale is important for finding the essential element of the higher efficiency and the wider oxygen content range in the application such as three-way catalysis or SOFC. In this study, the oxygen ionic transport properties of Sr3Fe2O7−δ are investigated as a function of its oxygen content by using density functional theory within the GGA+U methods. The calculated activation energy in Sr3Fe2O6.0 exhibits a higher migration barrier of 1.35 eV, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 51 publications
(67 reference statements)
3
30
0
Order By: Relevance
“…Structural optimization was carried out until the Hellmann-Feynman force on each atom was lower than 0.03 eVÅ À1 . All calculations were spin-polarized, 21,22 and the ferromagnetic (FM) states instead of antiferromagnetic (AFM) were used as indicated by Tadashi Ota et al 23 To predict the electronic structures more precisely, DFT + U method 24 was applied in all our calculations. Here, the value of U eff ¼ U À J ¼ 5.3 eV was applied for Fe ions, and the Coulomb (U) and exchange (J) parameters were not taken into account separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural optimization was carried out until the Hellmann-Feynman force on each atom was lower than 0.03 eVÅ À1 . All calculations were spin-polarized, 21,22 and the ferromagnetic (FM) states instead of antiferromagnetic (AFM) were used as indicated by Tadashi Ota et al 23 To predict the electronic structures more precisely, DFT + U method 24 was applied in all our calculations. Here, the value of U eff ¼ U À J ¼ 5.3 eV was applied for Fe ions, and the Coulomb (U) and exchange (J) parameters were not taken into account separately.…”
Section: Methodsmentioning
confidence: 99%
“…The conducting characteristics of Sr 3 Fe 2 O 7 is half-metallic, in good agreement with previous experimental and theoretical investigations on Sr 3 Fe 2 O 7 , facilitating the electron conduction. 12,23,29,30 To explore stable (001) surface for O 2 reduction investigation, ve types of (001) terminal surfaces can be clave, as illustrated in Fig. 2 and S1 † and noted as SrO-1, SrO-2, SrO-3, FeO-1 and FeO-2 terminal surfaces, respectively.…”
Section: Properties Of Sr 3 Fe 2 Omentioning
confidence: 99%
“…RP-type oxides Sr 3 Fe 2 O 7−δ have both superior NO x oxidation activity and NO x adsorption ability relative to the simple perovskite oxide SrFeO 3−δ . Recent X-ray absorption fine structure (XAFS) experiment 15 and the density functional theory (DFT) study 17 have revealed that the origin of superior catalytic activity of Sr 3 Fe 2 O 7−δ is attributed to the small activation energy for oxygen migration in bulk. Beyond these findings, the mechanism is still unknown for the NO x storage by the Sr-Fe perovskite.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Spiral magnetic order was observed by neutron diffraction 97 and provides a rare example of a magnetic cycloid arising from a ferromagnetic nearest neighbor competing with antiferromagnetic next-nearest exchange 98 . Further interest in this material arise from high oxygen mobility 99 . The preparation of a near stoichiometric compound requires high oxygen partial pressure 100 .…”
Section: Application Of Rvae To a Layered Perovskitementioning
confidence: 99%
“…68 Further interest in this material arise from high oxygen mobility. 69 The preparation of a near stoichiometric compound requires high oxygen partial pressure. 70 The rVAE analysis of SFO is shown in Figure 7.…”
Section: Bayesian Local Crystallographymentioning
confidence: 99%